2010
DOI: 10.1051/0004-6361/201015001
|View full text |Cite
|
Sign up to set email alerts
|

Dense molecular gas towards W49A: a template for extragalactic starbursts?

Abstract: Context. The HCN, HCO + , and HNC molecules are commonly used as tracers of dense star-forming gas in external galaxies, but such observations are spatially unresolved. Reliably inferring the properties of galactic nuclei and disks requires detailed studies of sources whose structure is spatially resolved. Aims. To understand the origin of extragalactic molecular line emission, we compare the spatial distributions and abundance ratios of HCN, HCO + , and HNC in W49A, the most massive and luminous star-forming … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 27 publications
(47 citation statements)
references
References 52 publications
5
42
0
Order By: Relevance
“…Williams et al (2004) argue that one cannot distinguish between a global collapse model of a large cloud and a multiple-cloud model, based on HCO + (J = 3-2 and 1−0) and C 18 O (J = 2-1) data. Roberts et al (2011) observe single-peaked HC 18 O + (J = 4-3) line profiles, which supports the large-scale infall hypothesis. In 13 CO and C 18 O J = 2-1 maps of the W49A region Peng et al (2010) find evidence of expanding shells with the dense clumps in the region lying peripherally along the shells.…”
Section: Introductionsupporting
confidence: 79%
“…Williams et al (2004) argue that one cannot distinguish between a global collapse model of a large cloud and a multiple-cloud model, based on HCO + (J = 3-2 and 1−0) and C 18 O (J = 2-1) data. Roberts et al (2011) observe single-peaked HC 18 O + (J = 4-3) line profiles, which supports the large-scale infall hypothesis. In 13 CO and C 18 O J = 2-1 maps of the W49A region Peng et al (2010) find evidence of expanding shells with the dense clumps in the region lying peripherally along the shells.…”
Section: Introductionsupporting
confidence: 79%
“…We selected these positions based on different kinematical signatures traced by dense gas tracers such as HCO + , HCN, and HNC (Roberts et al 2011), and are shown for example in Fig. 3.…”
Section: Line Identificationmentioning
confidence: 99%
“…This suggests the possible importance of PDR chemistry in W49A and may be tested using the ratio of CN/HCN, which is a well-known tracer of PDRs (e.g., Fuente et al 1996). The spatial distribution of HCN and its isotopomer HNC based on SLS data were analyzed in Roberts et al (2011). -C 2 H (ethynyl) is a commonly observed molecule in the interstellar medium, including in PDRs.…”
Section: Tracers Of Uv Irradiationmentioning
confidence: 99%
See 1 more Smart Citation
“…The targets are the Orion Bar, a prototypical photodissociation region ( Van der Wiel et al 2009); NGC1333 IRAS 4, a low-mass star-forming region; W49A, an active star formation complex (Roberts et al 2011); and the isolated high-mass star-forming region AFGL2591, which is the topic of this study. The SLS is complemented at higher frequencies (360)(361)(362)(363)(364)(365)(366)(367)(368)(369)(370)(371)(372)(373) The 16 receptors of the HARP receiver are distributed in a 4 × 4 pattern, regularly spaced at 30 intervals.…”
Section: Harp-b and The Jcmt Spectral Legacy Surveymentioning
confidence: 99%